Frontier Labourers, Crafts in Crisis and the Western Labour Revolt: The Case of Vancouver, 1900-1919 - Conley, James (Labour/Le Travailleur, 1989)
Abstract The case for systematic attention by labour historians to the crew list collection held in the Maritime History Archive of the Memorial University of Newfoundland is argued in terms of the historical interest of British maritime labour in the 19th and 20th centuries, and of the richness of the material itself. Maritime labour was characterised by a series of hiring practices and business dynamics which make it particularly worthy of attention. The impact of steam and steel technology, increased capitalization and government attention, and the emergence of a collective identity within the workforce, combine to produce a unique but important labour phenomenon which the existence of almost complete demographic and employment data bring well within the grasp of the historian. Various methodologies for studying the material are discussed, and the preferred method of studying the workforce of one large firm over a short period of time is illustrated with a brief case study.